Ketertarikan Tokoh Dilan Dalam Novel Milea : Suara Dari Dilan Karya Pidi Baiq Menggunakan Teori Humanistik Abraham Maslow - Maria Rosaria Wulan Purnamaningtyas; Maharani Kumala Chandra Devi; Eva Dwi Kurniawan (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
The purpose of this study is to describe Dilan's attraction in the novel Milea: Suara dari Dilan by Pidi Baiq using Abraham Maslow's humanistic theory. The approach method used to analyze the novel Milea is Abraham Maslow's multilevel needs approach. The results obtained in the research of characters in the novel Milea Suara dari dilan include various aspects including physiological needs, the need for security, the need for love and affection, the need for self-esteem and self-actualization. In this study, researchers used 4 needs including physiological needs, a sense of security, a sense of love and affection, and self-esteem. Researchers did not analyze using self-actualization needs because researchers did not find Dilan's character successfully achieving self-actualization.